STRATEGI PENGEMBANGAN SUMBER DAYA APARATUR PEMERINTAH DI BADAN LAYANAN UMUM DAERAH (BLUD) PROVINSI SUMATERA SELATAN - Muhammad Ridho; Susiani Susiani; Suwandi Suwandi; Hariyadi Hariyadi; Yeni Frendiana (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
The background of the research with the title "Strategy for Development of Government Apparatus Resources in the Regional Public Service Agency (BLUD) of South Sumatra Province", so far the South Sumatra Province BPSDMD in carrying out education and training for the State Civil Apparatus is only supported by APBD funds, so the volume of education and training is very large. limited. In the midst of the minimal budget allocation for the implementation of education and training in 2016 and 2017 budget efficiency. so that some of the planned activities could not be carried out, even in 2018 there was absolutely no allocation of funds for the training of the State Civil Apparatus in South Sumatra Province. The implementation of PPK-BLUD is effective since it was stipulated by Governor Decree Number 201/KPTS/BPKAD/2017 dated March 17, 2017 with Full BLUD status.The purpose of the application of the PPK-BLUD is to implement the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD) at the Regional Human Resources Development Agency of South Sumatra Province. As well as the Implementation of the Financial Management Pattern of Regional Public Service Agencies (PPK-BLUD) to increase the volume of performance of the Regional Human Resources Development Agency of South Sumatra Province. As well as making efforts or steps that need to be taken/recommended in an effort to improve and develop the Implementation of the Financial Management Pattern of Service Agencies Regional General Affairs (PPK-BLUD). The result of this research is that the implementation of PPK BLUD has been running in accordance with the applicable rules. so that the existing systematics must be consistent and clear (to be implemented or executed), because if the orders given change frequently, it can cause confusion for the implementers in the field. The implementation of PPK-BLUD has encouraged the improvement of service performance for BPSDMD of South Sumatra Province, namely the implementation of Tk II, Level III and Level IV Leadership Training, Basic Training Education and Training, Principal Training and Education and Training for Principal Strengthening. 2017Rp. 7,851,340,000 with the realization of 7,908,549,874 means that the target is achieved 100.73%. 2018 is the second year of the implementation of KDP-BLUD at the BPSDMD of South Sumatra Province, with a revenue target of Rp. 12,271,744,000 with a realization of Rp. 12,764,116.446,- While the revenue target for the 2019 implementation of the PPK-BLUD is Rp. 14,867,404,000 with a realization of Rp. 14,320,1442,500 as of December 27, 2019.. With the ease/flexibility of implementing PPK-BLUD not only pursuing remuneration, flexibility, avoiding laws and regulations in the procurement of goods/services, the application of PPK-BLUD is to improve the quality of public services, financial performance, and performance benefits for the community in a sustainable manner that is managed based on sound business practices.